Operator splitting for dissipative delay equations. Issue 1 (December 2014) - Bátkai, András; Csomós, Petra; Farkas, Bálint
Abstract Operator splitting methods for a special class of nonlinear partial differential equations with delay are investigated. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)